2022
DOI: 10.1136/bmjopen-2021-060270
|View full text |Cite
|
Sign up to set email alerts
|

Association between mental health and executive dysfunction and the moderating effect of urban–rural subpopulation in general adolescents from Shangrao, China: a population-based cross-sectional study

Abstract: ObjectivesTo examine the association between mental health and executive dysfunction in general adolescents, and to identify whether home residence and school location would moderate that association.DesignA population-based cross-sectional study.SettingA subsample of the Shanghai Children’s Health, Education, and Lifestyle Evaluation-Adolescents project. 16 sampled schools in Shangrao city located in downstream Yangtze River in southeast China (December 2018).Participants1895 adolescents (48.8% male) which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…As a result, with the same frequency of media use, urban elderly had higher levels of self-efficacy to improve health literacy than rural ones. Some previous studies discussed the urban-rural gap of self-efficacy (55) and the moderating effect of urban-rural residency (56), which was similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, with the same frequency of media use, urban elderly had higher levels of self-efficacy to improve health literacy than rural ones. Some previous studies discussed the urban-rural gap of self-efficacy (55) and the moderating effect of urban-rural residency (56), which was similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Regionally, we found that the prevalence of high blood pressure in urban areas was significantly higher than in suburban areas, which may be related to the higher consumption of fried and high-sugar foods leading to a higher probability of obesity in urban areas, [ 22 ] greater academic pressure in urban areas relative to suburbs, [ 23 ] and relatively less greenery and more severe air pollution in cities. [ 24 ] In terms of gender and age, the prevalence of high blood pressure showed a rapid upward trend after the onset of puberty, with greater fluctuations, especially among females, which is consistent with the results of Ye et al [ 25 ] We believe that this is related to the significant differences in hormone levels between childhood and puberty.…”
Section: Discussionmentioning
confidence: 99%
“…This study's demographic consists of university students enrolled in educational institutions located in the Chinese city of Shangrao. In the Shangrao region, these students represent a diverse cross-section of individuals pursuing higher education in a variety of disciplines and academic levels (Lin et al, 2022). The population of 6,579,714 students, consists of graduate students from various faculties and departments, each contributing unique perspectives and experiences to the communicationfocused study (Cucas, 2022;Guest et al, 2020).…”
Section: Methodsmentioning
confidence: 99%